2011
DOI: 10.1007/s10029-011-0889-7
|View full text |Cite
|
Sign up to set email alerts
|

Correct preoperative diagnosis of herniation through the Foramen of Winslow: two case reports

Abstract: We report two cases of one of the most infrequent types of internal abdominal hernias, i.e. incarcerated herniation through the Foramen of Winslow, with emphasis on appropriate preoperative radiological diagnosis using multidetector row computed tomography (MDCT) in both cases, and their successful surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 15 publications
0
30
0
5
Order By: Relevance
“…The protrusion of intra-abdominal viscera through the foramen of Winslow, a communication between the greater and lesser sac, is a type of herniation, since this peritoneal opening is normally kept shut by intra-abdominal pressure 6. The foramen of Winslow boundaries include the duodenum inferiorly, the caudate lobe of the liver superiorly, vena cava posteriorly and the hepatoduodenal ligament anteriorly, which contains, of note, the portal vein, common bile duct and hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protrusion of intra-abdominal viscera through the foramen of Winslow, a communication between the greater and lesser sac, is a type of herniation, since this peritoneal opening is normally kept shut by intra-abdominal pressure 6. The foramen of Winslow boundaries include the duodenum inferiorly, the caudate lobe of the liver superiorly, vena cava posteriorly and the hepatoduodenal ligament anteriorly, which contains, of note, the portal vein, common bile duct and hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
“…MDCT scans produce high-quality, multiplanar reconstruction (MPR) images using axial slices, which are able to identify the exact location of an internal hernia. González et al 6 reported two correct preoperative diagnoses of internal herniation through the foramen of Winslow, using MDCT. Furthermore, MDCTs have been shown to identify dead bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Foramen of Winslow hernia can be defined as peculiar variant of internal abdominal hernia, since it is a normal peritoneal orifice kept closed by normal intra-abdominal pressure that may be permeated by the intra-abdominal viscera [3]. …”
Section: Discussionmentioning
confidence: 99%
“…Various, more or less specific findings have been reported, such as an air-fluid collection in the lesser sac or signs of small bowel obstruction associated with the presence of mesenteric vessels stretching anterior to the inferior vena cava and posterior to the portal vein; the absence of the ascending colon in the right gutter and an antero-lateral displacement of the stomach [3]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation